Inflammation and immune cell abnormalities in intracranial aneurysm subarachnoid hemorrhage (SAH): Relevant signaling pathways and therapeutic strategies - Jin, Jing; Duan, Jian; Du, Leiya; Xing, Wenli; Peng, Xingchen; Zhao, Qijie (Frontiers in Immunology, 2022)
Intracranial aneurysm subarachnoid hemorrhage (SAH) is a cerebrovascular disorder associated with high overall mortality. Currently, the underlying mechanisms of pathological reaction after aneurysm rupture are still unclear, especially in the immune microenvironment, inflammation and relevant signaling pathways. SAH-induced immune cell population alteration, immune inflammatory signaling pathways activation and active substances generation are associated with pro-inflammatory cytokines, immunosuppression and brain injury. Crosstalk between immune disorders and hyperactivation of inflammatory signals aggravated the devastating consequences of brain injury, cerebral vasospasm, and increased the risk of infection. In this review, we discussed the role of inflammation and immune cells responses in the occurrence and development of aneurysm SAH, as well as the most relevant immune inflammatory signaling pathways [PI3K/Akt, extracellular signal-regulated kinase (ERK), hypoxia inducible factor-1α (HIF-1α), STAT, SIRT, mammalian target of rapamycin (mTOR), NLRP3, TLR4/nuclear factor-κB (NF-κB), and Keap1/nuclear factor (erythroid-derived 2)-like 2 (Nrf2)/ARE cascades] and biomarkers in aneurysm SAH. In addition, we also summarized potential therapeutic drugs targeting the aneurysm SAH immune inflammatory responses, such as nimodipine, dexmedetomidine (DEX), fingolimod, and genomic variation-related aneurysm prophylactic agent sunitinib. The intervention of immune inflammatory responses and immune microenvironment significantly reduces the secondary brain injury, thereby improving the prognosis of patients admitted to SAH. Future studies should focus on exploring potential immune inflammatory mechanisms and developing additional therapeutic strategies for precise aneurysm SAH immune inflammatory regulation and genomic variants associated with aneurysm formation.